Association of lung fluorodeoxyglucose uptake with radiation pneumonitis after concurrent chemoradiation for non-small cell lung cancer. (June 2017) - Yue, Jinbo; McKeever, Matthew; Sio, Terence T.; Xu, Ting; Huo, Jinhai; Shi, Qiuling; Nguyen, Quynh-Nhu; Komaki, Ritsuko; Gomez, Daniel R.; Pan, Tinsu; Wang, Xin Shelley; Liao, Zhongxing
Abstract: Background: Increased uptake of fluorodeoxyglucose (FDG) by lung tissue could reflect inflammatory changes related to radiation pneumonitis (RP). In this secondary analysis of a clinical trial, we examined potential associations between posttreatment lung FDG uptake and RP severity in patients with non-small cell lung cancer (NSCLC) for up to 12 months after concurrent chemoradiation (CRT). Methods: Subjects were 152 patients with NSCLC who had received concurrent CRT as part of the prospective trial NCT00915005. The following lung FDG variables were evaluated after CRT: maximum, mean, and peak standardized uptake values (SUVmax, SUVmean, SUVpeak) and global lung glycolysis (GLG; lung SUVmean × lung volume). RP severity was scored with the Common Terminology Criteria for Adverse Events v3.0. Results: Significant associations were noted between PET findings and RP severity at 1–6 months (all P  < 0.05), but not at 7–12 months after therapy (all P  > 0.05). Lung FDG uptake at 1–3 months after treatment predicted later development of grade ≥2 RP (all P  < 0.05), with cutoff values as follows: 4.54 for SUVmax, 3.69 for SUVpeak, 0.78 for SUVmean, and 2295 for GLG. Conclusions: Lung FDG uptake correlated significantly with RP severity during the first 6 months after CRT. The cutoff values seem clinically meaningful for identifying patients at risk of developing RP after such therapy.